MicroRNA-150 functions as a tumor suppressor and sensitizes osteosarcoma to doxorubicin-induced apoptosis by targeting RUNX2 - Ling, Zhonghua (Exp Ther Med, 2020)
Osteosarcoma (OS) is the most common form of bone malignancy in children and adolescents. MicroRNAs (miRNAs) have been associated with the development and progression of OS. In the present study, reverse transcription-quantitative PCR, western blotting, Cell Counting Kit-8, luciferase and Transwell assays were performed to investigate the biological function of microRNA-150 (miR-150) in OS. The results revealed that miR-150 was significantly downregulated in OS cell lines (HOS, SAOS2, MG-63 and U2OS) in comparison with the normal osteoblast cells (hFOB1.19). Overexpression of miR-150 significantly inhibited cell proliferation in OS cells. miR-150 could sensitize OS cells to chemotherapy treatment of doxorubicin. Runt-related transcription factor 2 (RUNX2) was identified as a target gene of miR-150. RUNX2 knockdown exhibited similar inhibitory effects on both OS cell proliferation and chemotherapy sensitivity. Restoration of RUNX2 reversed the biological function of miR-150. Finally, miR-150 overexpression and RUNX2 knockdown enhanced caspase-3 cleavage. Taken together, the present study established a novel molecular mechanism, in that miR-150 plays tumor suppressor and chemoprotective roles by targeting RUNX2 in OS, indicating that miR-150 may be a potential therapeutic target for OS therapy in the future.